2013
DOI: 10.3126/jpn.v3i6.8999
|View full text |Cite
|
Sign up to set email alerts
|

Lymphoid associated antigen expression in new cases of Acute Myeloid Leukemia

Abstract: Background: Occurrence of aberrant phenotype has been reported in acute leukemias with varying frequency though its prognostic importance remains controversial. In acute myeloid leukemias, aberrant phenotype, as high as 88 %, has been reported. To evaluate the occurrence of aberrant lymphoid phenotypes and to correlate their presence with various French American British classification, 100 cases of fresh acute myeloid leukemias were analyzed for lymphoid markers CD 4,7,8,10 and 19. Materials and Methods: Whole… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
2
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 17 publications
3
2
1
Order By: Relevance
“…whether included asynchronous antigens expression in addition to lymphoid associated antigens expression in AML cases 17 . Our figure of lymphoid antigens expression in AML (41.7%) is consistent with a previous study from Iraq (42%) 11 and approaching previous figures of 34.2% from Brazilm 18 , and 35% from India 19 ,but is lower than some other reported figures (47% -67.5%) [20][21][22] . CD56 was the most frequent lymphoid associated antigens expressed in our AML cases (13%).…”
Section: Discussionsupporting
confidence: 92%
“…whether included asynchronous antigens expression in addition to lymphoid associated antigens expression in AML cases 17 . Our figure of lymphoid antigens expression in AML (41.7%) is consistent with a previous study from Iraq (42%) 11 and approaching previous figures of 34.2% from Brazilm 18 , and 35% from India 19 ,but is lower than some other reported figures (47% -67.5%) [20][21][22] . CD56 was the most frequent lymphoid associated antigens expressed in our AML cases (13%).…”
Section: Discussionsupporting
confidence: 92%
“…The frequency of aberrant expression in AML in our study was 19.9% and this is in accordance to the results of some studies in which the aberrant expression ranged from 11.1% to 26.4% of AML cases (1,16,27,36,49). Many other studies reported higher frequency of aberrant expression among their AML patients between 30% -67.5% (13, 18,30,41,[50][51][52][53][54][55]. This variation in frequency of aberrant phenotypes in AML among different studies may be depending upon the markers studied, sample size or criteria of aberrancy used.…”
Section: Aberrant Expression In Aml Patientssupporting
confidence: 91%
“…CD7, a T-cell antigen known to show aberrant expression was most commonly expressed in our study (26.4%) followed by CD19 (1.2%). The same trend was observed in most of the international studies where CD7 was most commonly expressed aberrant antigen followed by CD19 2,8,14,16,20. CD7 expression in AML is correlated with lower incidence of complete remission 2.…”
Section: Discussionsupporting
confidence: 79%